2011
DOI: 10.1108/17515631111100412
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between human resource practices and firm performance: an empirical assessment of firms in Malaysia

Abstract: PurposeThe objective of this study is to gain more insight into Malaysian human resource management, in terms of its history and current HR practices. Also, this paper also intends to examine the impact of implementing HR practices on the overall organization's performance based on a sample of 217 Malaysian based companies.Design/methodology/approachData were collected via questionnaires from human resource managers and top executives responsible for the managing human resources in their respective organizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 12 publications
4
45
1
1
Order By: Relevance
“…Regarding the positive impact of HRM practices on OP found in this study, similar results have been revealed in the literature (e.g. Amin et al, 2014;Chan & Mak, 2012;Chand & Katou, 2007;Moideenkutty et al, 2011;Osman et al, 2011). Inconsistently, Kuo (2011) found a non-significant direct relationship between HRM practices and OP.…”
Section: Hypotheses Testingsupporting
confidence: 76%
“…Regarding the positive impact of HRM practices on OP found in this study, similar results have been revealed in the literature (e.g. Amin et al, 2014;Chan & Mak, 2012;Chand & Katou, 2007;Moideenkutty et al, 2011;Osman et al, 2011). Inconsistently, Kuo (2011) found a non-significant direct relationship between HRM practices and OP.…”
Section: Hypotheses Testingsupporting
confidence: 76%
“…Again, one study by Islam and Siengthai (2010) in Bangladesh industries in DEPZ area with 53 samples 216 respondents, the result of the study revealed that training and development is significantly related to performance. While, some studies shown that there are indirect and insignificant relationship between training and development and organizational performance (Osman, Ho, & Carmen Galang, 2011;Vlachos, 2008). The present study hypothesizes that:…”
Section: Training and Developmentmentioning
confidence: 76%
“…For instance, the study conducted by Islam and Siengthai (2010) in Dhaka Export Processing Zone (DEPZ) Bangladesh, using 53 samples of Enterprises with 216 respondents, a quantitative regression analysis findings revealed that performance appraisal is positively related to performance. Similarly, the survey research conducted by Osman et al (2011) using Performance appraisal and firm performance in Malaysia with 800 different industry sectors, the regression result shows significant positive relationship on performance. However, one study explained contrary to the aforementioned studies, were insignificant relationship revealed in the findings (Meier & O'Toole, 2013).…”
Section: Performance Appraisalmentioning
confidence: 99%
“…Gringore, 2008;Bau & Dowling, 2007;Ukenna et al, 2010;Daud, 2006;Hemdi, 2005;Osman, Ho, & Galang, 2011b;Othman, 2009;Othman et al, 2001;Rowley & Abdul-Rahman, 2007). There is dearth of research on HRM-SMEs relationship, most especially in the context of Nigeria (Ojukuku, 2012).…”
Section: Hpws-smes Performance Nexus In the Context Of Smesmentioning
confidence: 99%
“…Given all these facts, it is imperative to examine whether HRM-performance nexus is contingent on another variable, most especially in a context, such as SMEs, where there is dearth of HRM research, since most of the research focused on large organizations (e.g. Ukenna et al, 2010;Osman et al, 2011b;Othman, 2009). …”
Section: Introductionmentioning
confidence: 99%